Kartu Kredit Syariah: Perspektif Hukum Islam - Imam Wahyu Hardiansyah (STAI Auliaurrasyidin Tembilahan, 2021)
Credit cards are one of the most common methods of payment in modern society. Credit cards are used to replace payments for the purchase of products and services. In cities, the Public usually uses this credit card to shop at retail stores and malls. The rapid development of the use of credit cards currently because people feel the cards as a means of payment and taking cash considering the practicality, comfort, and security. The basic law of sharia charge cards, however, has been explained in the Quran, Hadith, and also Ijma'.